Evaluating UI/UX Online Courses : A Case Study Of Software Engineering Students’ Learning Experience - Rasendriya, Achmad Syahmi; Najla Amelia Putri; Anatasya Wenita Putri; Aulia Anggraeni; Jonathan Cristiano Rabika; Muhammad Al Amin; Barus, Irma Rasita Gloria; Amata Fami (SAINTEKBU, 2024)
With technology advancing quickly in today's world, education has become one of the significantly affected aspects. Technological progress facilitated access to educational materials, leading to the emergence of various new learning methods, including online courses. Online courses were widely favoured due to the customization and diverse variations of their learning materials. Visual design, user interface (UI), and user experience (UX) played a crucial role in attracting interest in learning, as evidenced by increased engagement among users of online courses with appealing designs. These critical UI/UX aspects provided a specific boost in understanding and exploring this field, as reflected in the provision of UI/UX materials on online course platforms. This study utilized the User Experience Questionnaire (UEQ) method to evaluate the satisfaction and experiences of students participating in UI/UX online courses across six aspects: Attractiveness, Efficiency, Perspicuity, Dependability, Stimulation, and Novelty. The study involved 41 students who took UI/UX online courses for one month. The results indicated a high level of satisfaction across these aspects, suggesting that UI/UX online courses could be considered effective and reliable methods for understanding and exploring this field.